THE IMPLEMENTATION OF NEW LEARNING TECHNIQUES METHODS OF " SKI PARALLEL TURN" WITH ROTATION IN ALPINE SKIING - Paţa Oana Cristina (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
The paper proposes the application of an algorithmic route of new techniques in basic learning, especially parallel turns in alpine skiing by using " turn learning machine "to the youngest skiers, beginners" . The application of specific means methodology of exercises with the" turn learning machine " helps assimilating the rotation, in a short time and with high quality index. The proper learning procedure of the parallel turn with rotation using turn learning machine ", enables the efficient downhill evolution of new skiers, regarding the ability to properly go through the marked gates, in optimal time units. Mise en œuvre de nouvelles méthodes d'apprentissage des techniques de "parallel turn with rotation " to alpin skiing.